SISTEM INFORMASI FORUM KONSULTASI MAHASISWA PADA AMIK WAHANA MANDIRI TANGERANG BERBASIS WEB - Yasin Efendi (LPPM Universitas Bina Bangsa, 2022)
By this time computers were already an indispensable part of human life. The role of computers is felt in almost all areas of life, especially along with the rapid development of computer network technology, all the information we need can be obtained in just a short time. One of the protocols used for communication between one computer and another is HTTP (Hyper Text Transfer Protocol) which is a protocol used by all web-based systems. In this study, we will discuss the design of a web-based student consultation forum information system at AMIK Wahana Mandiri Tangerang Selatan. This system is an application system for student activities in consultations that are carried out manually to be more effective, accurate and computerized. So that the processing and storage process can be easier and more efficient. This system is designed with UML (Unified Modelling Language) modeling consisting of Use Case Diagrams, Class Diagrams, Activity Diagrams, and Sequence Diagrams. The implementation results of this research are expected to be useful for AMIK Wahana Mandiri, especially for student consultation activities at AMIK Wahana Mandiri